A Pilot Study Exploring the Optimization of Warm-Up Strategies: Modern Cognitive Warm-Up with Open-Skill Demands vs. Traditional Closed-Skill Warm-Up in Basketball - Asaf Shalom; Roni Gottlieb; Ido Shalom; Guy Gafni; Aviad Levy; Julio Calleja-Gonzalez (Sensors)
Warm-up protocols are essential in high-intensity sports such as basketball, in which explosive power and rapid decision-making are critical for performance. This study examined the immediate effects of a modern cognitive warm-up, incorporating open-skill demands and cognitive-motor dual tasks, compared to a traditional closed-skill warm-up in youth basketball players. Twelve male players (ages 15–16) from an elite Israeli youth basketball club participated in the study and performed performance assessments post-warm-up. Sprint performance was evaluated using a closed-skill test (CST: 5-m and 10-m sprints without external stimuli) and an open-skill test (OST: 5-m and 10-m sprints with a reaction-based stimulus). The modern cognitive warm-up integrated advanced sports technology, and all performance assessments were conducted using reliable measurement technologies. The results demonstrated that the modern cognitive warm-up significantly enhanced sprint performance in both OST (p < 0.01) and CST (p < 0.05 for 5 m sprint), with no significant difference in the 10 m CST. Reaction times were also significantly improved (p < 0.01), emphasizing the effectiveness of cognitive warm-ups in enhancing perceptual-motor readiness. These findings suggest that integrating cognitive-motor dual tasks and open-skill elements into warm-up routines may enhance both readiness and focus for explosive performance, as well as improve players’ reactive abilities.